KINERJA CAMPURAN ASPAL PORUS DENGAN SUBTITUSI LIMBAH BETON SEBAGAI BAHAN RAMAH LINGKUNGAN - Sa'dillah, M. - (Jurnal Ilmiah Teknik Sipil; Vol 25 No 2 (2021): Jurnal Ilmiah Teknik Sipil, Vol. 25 No. 2, Juli 2021DO - 10.24843/JITS.2021.v25.i02.p06, 2022)
Contribution of concrete waste to construction waste is quite large. This is in line with the increasing activity of building construction. In Indonesia, concrete waste is usually not used properly. Most of it is dumped in the open field and some is used as fill material. The availability of these materials is quite a lot. So the potential for recycling is very possible. The purpose of this study was to determine the effect of adding waste concrete in the optimum mixture of porous asphalt on Marshall characteristics. The research will be conducted using the Australian Asphalt Pavement Association (AAPA) 2004 approach. The method is used because porous asphalt is a type of pavement that has an open gradation so that it is in accordance with the specifications. Determination of the optimum level of porous asphalt concrete waste with concrete waste is determined from the relationship of several porous asphalt testing parameters with the required standards. From the graph of determining the level of concrete waste above, it shows that at levels of concrete waste 0%, 40%, 60%, 80% and 100% all meet the specifications specified by the Australian Asphalt Pavement Association (AAPA) 2004. From taking the middle value that meets the specifications From these results, it can be concluded that the use of concrete waste as a porous asphalt mixture meets the marshall characteristics and the permeability has an optimum concrete waste content of 60%.